The Response of International Campaign to Ban Landmines (ICBL) to Resolve the Problem of Humanitarian Issue - Putri, Alfredha Shinta (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
This research aims to explain the role of International Non-Governmental Organization (INGO) namely ICBL (International Campaign to Ban Landmines). The objective of ICBL to overcome the problem of landmines as an emergency problem and critical issue in the world. This matter is because the effect of landmines and explosive remnants of war is very dangerous for humans, animals, and other living things. Otherwise, ICBL engage all of the states in the world to ratify an international agreement to ban using and producing landmine through The Mine Ban Treaty which agreed in 1997 by the states in the world. The efforts of ICBL are supported by United Nations and other advocacy networks. The obstacles arise from the unwillingness of great power to sign and ratify The Mine Ban Treaty. But, although still deal with some obstacles and challenges, ICBL able to decrease the amount of landmines in the world today. The research used secondary sources collected from books, journal, article, or other related-website.